Philip Melanchthon’s Early Theology of Preaching: Theologizing the Word of God in His Apology of the Augsburg Confession (1531) - Simuţ, Corneliu C. (The expository times, 2017)
This paper focuses on how Philip Melanchthon organized his theology of preaching in the Apology of the Augsburg Confession, the very first defense of the early church reformers’ approach to doctrine against formal papal criticism as drafted in the Confutation of the Augsburg Confession by Johann Eck, who had been commissioned by emperor Charles V to provide a papal romanist refutation of the reformist Augsburg Confession. The article is going to demonstrate that Melanchthon’s theology of preaching insists on the proclamation of God’s Word as Christ, Gospel, and repentance, an indication that his homiletical theory encompasses key dogmas like christology, revelation, and soteriology, all fundamental tenets which not only define the core of Protestant theology and practice but also provide listeners with the possibility of a changed life experience based on Christ’s work as savior. The main contribution of this paper resides in the fact that on the one hand, it attempts to clarify Melanchthon’s theological position not as a Protestant writing against Catholics but rather as reformist challenging his papal peers within the Catholic church, while on the other hand, it identifies various aspects of his early thought as presented in the Apology—Christ, Gospel, repentance—and places them together systematically into a building block which constitutes his early theology of preaching as dogmatically founded on as well as anchored in christology, revelation, and soteriology.